Szkoła Prawa Hiszpańskiego - Bazylińska-Nagler, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The School of Spanish Law initiated teaching on the 6th of February 2012 after the founding agreement of the 26th of January 2012 had been concluded by and beetween: Universidad Autónoma de Madrid and University of Wrocław. Desiring to enable Polish students and universities’ graduates to gain knowledge on Spanish law, Universidad Autónoma and University of Wrocław had decided to establish the School of Spanish Law at the Faculty of Law, Administration and Economics of the University of Wrocław under the law applied in the place where the activity takes place.The School had been founded to provide its students with basic knowledge on Spanish legal system and Spanish Legal Language involving academic teachers from both universities. The School is targeted at international exchange of the cooperating Universities’ academic teachers. The main scope of activities of the School is teaching various Spanish Law disciplines, however the founding agreement encompasses other forms of academic activities too — i.e. summer law schools. In practical terms lectures in the School are scheduled for two following semesters. Universidad Autónoma delegates 10 Professors to give approx. 90 hours of lectures in two semesters. Professors provide students with materials of instruction, prepare and conduct the exams. Students who successfully complete the School of Spanish Law programme receive a certificate signed by the Dean of WPAiE UWr, the Dean of the Faculty of Law of UAM and the Head of the School.
Keywords: Szkoła Prawa Hiszpańskiego; Wydział Prawa Administracji Ekonomii UWr; historia